Cyclization, Decyclization, and Metallacyclization of Pyridine‐Substituted Homopropargylic Alcohols on Ruthenium(II) and Osmium(II) Centers - Shek, Hau‐Lam; Yeung, Chi‐Fung; Chung, Lai‐Hon; Tse, Man‐Kit; Yiu, Shek‐Man; Wong, Chun‐Yuen (Chemistry : a European journal, 2023)
Systematic investigations on the reactions between cis‐[M(dppm)2Cl2] (M=Ru/Os; dppm=1,1‐bis(diphenylphosphino)methane) and pyridine/quinoline substituted homopropargylic alcohols uncovered the diverse Ru(II)/Os(II)‐induced alkyne activation pathways. The alkynes underwent cyclization on M via a “non‐vinylidene” pathway at lower temperatures, resulting in alkenyl intermediates which might further metallacyclize to give metallapyrroloindolizines. Conversely, reactions at higher temperatures induced alkyne cyclization on M via a “vinylidene” pathway, affording cyclic oxacarbene complexes. Additionally, a rare decyclization mechanism was observed during the transformation of a metallacyclization‐resistant alkenyl complex into a cyclic oxacarbene complex. DFT calculations were employed to validate the experimental findings. Overall, these results not only provide insights into controlling alkyne activation pathways, but also offer new strategies for preparing metalated heterocyclic and metallacyclic complexes. Experimental and theoretical investigations on the reactions between cis‐[Ru/Os(dppm)2Cl2] and pyridine/quinoline‐substituted homopropargylic alcohols provided strategies to prepare new metalated heterocyclic and metalacyclic complexes by utilizing temperature‐controlled divergent pathways and an unexpected decyclization mechanism. Cyclization, decyclization, and metallacyclization of pyridine‐substituted homopropargylic alcohols on ruthenium(II) and osmium(II) centers (C. Y. Wong et al.)